Crypto Currency Prediction Model using ARIMA - G. Vidyulatha, M. Mounika, N. Arpitha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Over the past few years, Bitcoin has been a topic of interest of many, from academic researchers to trade investors. Bitcoin is the first as well as the most popular cryptocurrency till date. Since its launch in 2009, it has become widely popular amongst various kinds of people for its trading system without the need of a third party and due to high volatility of Bitcoin price. Thus, this article presents a suitable model that can predict the market price of Bitcoin best by applying a few statistical analyses. Our work is done on five and half year’s bitcoin data from 2015 to 2020 based on time series analysis approachcalled autoregressive integrated moving average (ARIMA) model. Further, it is also compared to existing machine learning algorithm named linear regression (LR) model. Extensive prediction results shown that the proposed ARIMA model acquiredsuperior performance for deciding volatility in weighted costs of bitcoin in the short run as compared to LR model.